Nitrogen Incorporation in TiO2: Does It Make a Visible Light Photo-Active Material? - B. Viswanathan; K. R. Krishanmurthy (International Journal of Photoenergy)
The possibility of hydrogen production by photo-catalytic decomposition of water on titania has provided the incentive for intense research. Titania is the preferred semiconductor for this process, in spite of its large band gap (~3.2 eV) that restricts its utility only in the UV region. Various sensitization methodologies have been adopted to make titania to be active in the visible region. Doping of TiO2 with nitrogen is one such method. The purpose of this presentation is to examine the state and location of nitrogen introduced in TiO2 lattice and how far the shift of optical response to visible radiation can be beneficial for the observed photo-catalysis. The specific aspects that are discussed in this article are: (i) N-doped titania surface adopts a non-native configuration, though the bulk material is still in the native configuration of pure TiO2 (ii) Though the nitrogen doped materials showed optical response in the visible region, the changes/improvements in photo-catalytic activity are only marginal in most of the cases. (iii) The exact chemical nature/state of the introduced nitrogen, and its location in titania lattice, substitutional and/or interstitial, is still unclear (iv) Is there a limit to the incorporation of nitrogen in the lattice of TiO2?